GC-MS analysis of aromatic compounds from leaves of Colebrookea oppositifolia Smith. - Sardar PR; Manik SR (International Journal of Life Sciences, 2017)
Plants synthesize substances that are useful for the maintenance of health in humans and other animals. The Lamiaceae (Labiatae) is one of the diverse and widespread plant families in terms of ethnomedicine and its medicinal value is based on the volatile oils concentration. The Lamiaceae is one of the largest families among the dicotyledons, many species belonging to the family being highly aromatic, due to the presence of external glandular structures that produce volatile oil. This oil is important in pesticide, pharmaceutical, flavouring, perfumery, fragrance and cosmetic industries. Colebrookea oppositifolia Smith belonging to the family Lamiaceae is commonly known as Indian Squirrel Tail (English),Binda (Hindi). The plant grows wild on hills & plains throughout India.The plant material is generally used to cure the diseases like epilepsy, fever, headache, and urinary problems.The present paper deals with the important aromatic phyto-constituents obtained from Colebrookea oppositifolia identified as Phytol, n-Hexadecanoic acid, 9,12,15 Octadecatrienoic acid, 2-Dodecen-1-ny,succinic anhydride, Octanoic acid tridec-2eny ester.